Enhancing Operational Efficiency in Culinary MSMEs through Profit-Sharing Based Working Capital - Sarwono; Erwina Kartika Devi (CV. Civiliza Publishing, 2025)
Culinary MSMEs often face structural challenges regarding financial instability and rigid debt obligations that hinder operational growth. This study explores how profit-sharing based working capital enhances operational efficiency, using the cassava chip industry in Geragai District, Tanjung Jabung Timur, as a case study. Employing a qualitative case study design with purposive sampling, data were collected through in-depth interviews, field observations, and financial document reviews, then analyzed using thematic analysis. The results indicate that the profit-sharing model acts as a